A regional assessment of the operational National Water Model in the San Francisco Bay area for the 2018–2019 water year - Jungho Kim; Eunsaem Cho; V. Chandrasekar; Rob Cifelli; Lynn E. Johnson; Andy Wood; David Gochis (Journal of Hydrology, 2025)

Intercomparison of the U.S. National Water Model with OpenET over the Bear River Basin, U.S. - Ayman Nassar; David Tarboton; Martha Anderson; Yun Yang; Joshua B. Fisher; Adam J. Purdy; Furqan Baig; Cenlin He; David Gochis; Forrest Melton; John Volk (Journal of Hydrology, 2025)

Simulation of groundwater-flow dynamics in the U.S. Northern High Plains driven by multi-model estimates of surficial aquifer recharge - Farshid Felfelani; Joseph Hughes; Fei Chen; Aubrey Dugger; Tim Schneider; David Gochis; Jonathan Traylor; Hedeff Essaid (Journal of Hydrology, 2024)

An experiment on reservoir representation schemes to improve hydrologic prediction: coupling the national water model with the HEC-ResSim - Jungho Kim; Laura Read; Lynn E. Johnson; David Gochis; Rob Cifelli; Heechan Han (Hydrological Sciences Journal, 2020)

Ocean–atmosphere conditions related to severe and persistent droughts in the Mexican Altiplano - José Pablo Vega‐Camarena; Luis Brito‐Castillo; Luis M. Farfán; David J. Gochis; Luis F. Pineda‐Martínez; Sara C. Díaz (International Journal of Climatology, 2018)
Ocean and atmospheric patterns associated with the most severe and most persistent droughts in the Mexican Altiplano region are explored. The standardized precipitation index on a time scale of 12 months was used and compared with time series of other atmospheric conditions to identify major dry episodes from 1970 to 2012. The time series were derived from the second mode of a varimax‐rotated empirical orthogonal functional analysis from the mean summer rainfall series observed at weather stations located in the Mexican Altiplano from 1970 through 2000. The results showed that the longest and most persistent episode occurred from 1998 through 2001, while the most severe dry episode occurred in 2011–2012, when the Pacific Decadal Oscillation was in a negative phase and the Atlantic Multidecadal Oscillation in a positive phase, both in combination with a La Niña event. A large upper‐level anticyclone over the north‐central United States is related to droughts in the Altiplano. Under these conditions, the droughts were linked to a large anticyclone positioned over the central‐north of the United States, with consequent negative anomalies of specific humidity over central‐northern Mexico. Concurrent with droughts in the interior of Mexico, are positive rainfall anomalies along the central Pacific coast of Mexico near the study area. Under different atmospheric conditions, opposite anomalous behaviour between the coast and interior can exist. The mechanism driving this see‐saw behaviour between the west coast of Mexico and the Altiplano is explored.

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Evaluating the hydro-estimator satellite rainfall algorithm over a mountainous region - Ismail Yucel; Robert J. Kuligowski; David J. Gochis (International Journal of Remote Sensing, 2011)

Correlations between sea‐surface temperatures and warm season streamflow in northwest Mexico - David J. Gochis; Luis Brito‐Castillo; W. James Shuttleworth (International Journal of Climatology, 2007)
Previous hydroclimatological analysis of the North American Monsoon (NAM) region of northwest México revealed significant sub‐regions of coherence in seasonal precipitation and streamflow. In this work, interannual variations in regionalized streamflow and rainfall‐runoff relationships are explored. Modulation of the monsoon hydroclimatology by large‐scale forcing mechanisms such as tropical, North Pacific, and Caribbean Sea‐surface temperature perturbations results in nonlinear responses in seasonal runoff that varies by region. Analyses reveal that the El Niño‐Southern Oscillation (ENSO) exerts a modest but statistically significant influence on NAM streamflow. Different sea‐surface temperature and sea‐level pressure indices exhibit markedly different lag‐correlation structures in different NAM streamflow regions and these relationships vary significantly according to the decadal scale sea‐surface temperature (SST) variability in the North Pacific. The structure of correlation patterns between eastern Pacific SST and regionalized NAM streamflow anomalies complicates the application of common ENSO indices as streamflow predictors. The occurrence of ENSO also has a significant impact on regional runoff fractions and on the partitioning of streamflow between the summer and winter seasons. The summer ENSO influence is explained, in part, by changes in the lower tropospheric pressure and wind fields, which result in modest increases in atmospheric moisture over the streamflow regions during La Niña episodes versus El Niño episodes. The results suggest that improved monitoring and prediction of ENSO variability, through careful development of eastern Pacific SST indices in the pre‐monsoon period should provide useful guidance for seasonal forecasts of regional monsoon streamflow. Copyright © 2006 Royal Meteorological Society